A multi-agent framework for stock trading. (15th May 2009) - Rahimi, Shahram; Tatikunta, Raju; Ahmad, Raheel; Gupta, Bidyut
TrAgent is a secure multi-agent environment which models a stock exchange such as the New York Stock Exchange and the procedure of trading securities on the trading floor. The model comprises the complete process from the initiation of a trading order until its execution and also deals with the security issues involved. The multi-agent paradigm is the framework for implementation of the system. The properties of intelligent software agents meet the characteristics of the actors on the trading floor and provide capabilities for efficient distributed computing. These characteristics include dynamic and flexible adoption to a changing scene, asynchronous and autonomous behaviour, and efficient use of resources in a distributed environment. The main focus in this paper is on one of the important agents in TrAgent, the stock broker agent. Intelligence is provided to the stock broker agent in order to make decisions and give reasons on the profitability of a firm. This intelligence is formed using fuzzy expert system. The paper further discusses the implementation issues concerning different components of the model and their security framework.